ANALISIS PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN RETAIL TRADE YANG TERDAFTAR DI BEI TAHUN 2014-2017 - Santoso, Prihatin Gatot; Simamora, Saur Costanius (JURNAL ILMIAH M-PROGRESS, 2019)
This study aims to predict financial distress conditions experienced by retail trade companies listed on the Indonesia Stock Exchange in the period 2014-2017. The population in this study is a retail trade company listed on the Indonesia Stock Exchange for the period 2014-2017. Total sample are seventeen retail trade companies, namely ACES, AMRT, CENT, CSAP, ECII, ERAA, GOLD, HERO, KOIN, LPPF, MAPI, MPPA, RALS, RANC, RIMO, SONA, TELE. Type of descriptive research. The results of the calculation of financial distress analysis with the Altman Z-Score method explain consistently that companies that experience financial distress are CENT (2014-2017), GOLD (2015-2017), and RIMO (2014-2016). While companies experiencing grey area conditions are CSAP (2014-2017), ECII (2015-2017), GOLD (2014), and MPPA (2016-2017).Keywords: financial distress, Altman Z-Score method, financial ratio